Awareness Regarding Health Effects of Pesticides Use among Farmers in a Municipality of Rupandehi District - Gurung, Saraj; Kunwar, M (Journal of Universal College of Medical Sciences, 2018)
INTRODUCTION: Pesticides are natural or synthetic agents that are used to kill unwanted plant or animal pests. Pesticides use is the most attractive method of controlling pest which involves less labour and characterised higher outcome per hector of land. Extensive use of such pesticides results in substantial health and environmental threats. MATERIAL & METHODS: Descriptive cross-sectional design was used for the study to find out awareness regarding health effects of pesticides use. Fifty vegetable farmers were selected as the study sample by non purposive and snow ball sampling technique. Pretested structured interview schedule was used for data collection and analyzed by using descriptive statistics. RESULTS: The findings of the study revealed that respondents were aware that skin irritation (96%), dermatitis (92%), dizziness (98%), headache (96%) as poisoning symptoms in skin and nervous system. Respondents were aware nausea (84%), vomiting (96%), dyspnoea (88%), and throat itching (76%) as poisoning symptoms in gastro-intestinal and respiratory system. Respondents were also aware that eye irritation (96%) and burning (90%), and tachycardia (90%) as poisoning symptoms of pesticide use in eye and cardio vascular system. They were aware that use of pesticides may cause cancer (88%), foetal death (74%), infertility (66%), birth defects (66%) and miscarriage (56%) as long term effects. Cent percent of respondents were aware that washing exposed part with soap water, taking bath and changing clothes asimmediate actions after pesticides contact with body CONCLUSION: Based on the findings of the study more than half of respondents had low level of awareness regarding health effects of pesticides use. So, it is recommended to organize awareness program to the farmers regarding health effects of pesticides use. Journal of Universal College of Medical Sciences, Vol. 5, No, 2, 2017, Page: 18-21